PIERRE-FELIX BOURDIEU'S PHILOSOPHICAL BASIS IN LITERARY STUDIES - Harendika, Melania Shinta (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
The concepts of Pierre-Felix Bourdieu regarding capital, habitus, and fields are often found in literary studies. However, only a few studies examine the basic assumptions behind these concepts. This study discusses Bourdieu's assumptions about individuals, society, authors, literary works, and literary studies to be accepted entirely. This study adopts the perspective put forward by Ahimsa-Putra. A literature review, used as a research method, helps the author describe these basic assumptions comprehensively. This study reveals that individuals have strengths and perspectives that determine their strategy in social life. This strategy is required to survive because Bourdieu said society is a game. In this case, the game also influences literary works. Bourdieu created two poles: autonomous and heteronomous between intellectuals and authors. Therefore, the literature study requires in-depth observation methods to describe it clearly.